(untitled) (Czech Journal of Multidisciplinary Innovations, 2024)
This article examines the application of computer simulation models (CSMs) and media education in teaching Japanese kanji, focusing on how innovative technologies can enhance learning effectiveness. It discusses the shift from traditional, teacher-centered methods to modern approaches that promote independent learning, critical thinking, and student engagement. CSMs offer an interactive platform that aids in the comprehension and retention of complex kanji characters, integrating mnemonic techniques and visual models to improve memorization. The article also highlights the role of media tools, such as YouTube and Telegram, in facilitating distance learning and fostering media literacy skills among students. Through a combination of CSMs and media education, students can more effectively master kanji, while teachers benefit from reduced workload and improved instructional efficiency. The integration of these technologies into the curriculum not only enhances the teaching and learning process but also prepares students for active participation in the information-rich, media-driven society